Determination of types of fat ingredient in some commercial biscuit formulations - Abdul Manaf, Yanty Noorzianna; Marikkar, Jalaldeen Mohammed Nazrim; Mohammed, Abdulkarim Sabo (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2014)
A study was carried out to compare the composition and thermal profiles of the fat component of six brands of commercial biscuits (BA, BB, BC, BD, BE & BF) with those of lard and palm oil. Extraction of fat from biscuit samples was done using petroleum ether according to the soxhlet extraction procedure. The isolated fat samples along with lard and palm oil were analyzed using gas liquid chromatography (GLC), reversed-phase high performance liquid chromatography (RP-HPLC), and differential scanning calorimetry (DSC). According to GLC analysis, palm oil, lard and all six biscuit brands had either palmitic or oleic acid as major fatty acids. Sn-2 positional analysis of fatty acids showed that oleic (> 60%) as the most dominant fatty acid of palm oil and biscuit brands BA, BB, BC, and BD while palmitic (> 60%) as the most dominant fatty acid of lard and biscuit brands BE and BF. RP-HPLC analysis showed that the triacylglycerol (TAG) profiles of lard and biscuit brands BE and BF were closely similar while those of brands BA, BB, BC, and BD and palm oil were similar. DSC analysis showed that the cooling and heating profiles of lard and brands BE and BF were similar, while those of palm oil and brands BA, BB, BC, and BD were similar. Hence, this study concluded that biscuit brands BE and BF are not suitable for consumers whose religious restriction prohibit the use of lard as food ingredient.